Julie's journey - McDonald, Megan; Hunt, Robert, 1952- (Middleton, WI : American Girl, 2007)
Julie and her cousins set out on an old-fashioned wagon train to celebrate the Bicentennial, and Julie is unprepared for the challenges of prairie life, but when she and her cousins have a chance to make history, Julie rises to the challenge.
"American girl"--Cover.
"1974."
4.5
3-6
Keywords: American Revolution Bicentennial, 1976 -- Juvenile fiction; Wagon trains -- Juvenile fiction; Family -- California -- San Francisco -- Juvenile fiction; San Francisco (Calif.) -- History -- 20th century -- Juvenile fiction; American Revolution Bicentennial, 1976 -- Fiction; Wagon trains -- Fiction; Family life -- California -- San Francisco -- Fiction; San Francisco (Calif.) -- History -- 20th century -- Fiction; American Revolution Bicentennial, 1776-1976 -- Fiction; Wagon trains -- Fiction; Family life -- San Francisco (Calif.) -- Fiction; San Francisco (Calif.) -- History -- Fiction